Aquaporin-4 antibodies, CNS acidosis and neuromyelitis optica: a potential link - Jarius, Sven; Wildemann, Brigitte (Medical hypotheses, 2013)
Background - Neuromyelitis optica (NMO, Devic’s syndrome) is a severely disabling disorder of the central nervous system characterized by optic neuritis and longitudinally extensive myelitis. In around 80% of cases, NMO is caused by autoantibodies to astrocytic aquaporin-4 (AQP4), the most abundant water channel in the CNS. Acute NMO attacks are frequently accompanied by elevated levels of lactate in the cerebrospinal fluid (CSF). As a strongly dissociated anion (pK′=3.7) directly changing the strong ion difference, lactate causes a reduction in the dependent anion [HCO3-] and a rise in [H+], resulting in “metabolic” acidosis in the CSF. CSF acidosis also develops during respiratory failure due to brainstem or high cervical spinal cord lesions, the most common cause of death in NMO. However, lactic acid and more generally, a decrease in pH, has been shown to increase the membrane expression of AQP4 in astrocytes. An increase in AQP4 membrane expression during acute NMO attacks could potentially enhance the complement-mediated humoral immune reaction against AQP4-expressing astrocytes characteristic for NMO and, thus, result in more severe astrocytic damage. Moreover, lactate and acidosis have been shown to cause astrocytic swelling and to affect astrocytic viability, potentially rendering astrocytes more susceptible to AQP4-Ab-mediated damage. Finally, increased AQP4 expression could be an independent risk factor in NMO and other forms of CNS inflammation, as indicated by the finding of grossly attenuated experimental autoimmune encephalomyelitis in AQP4-null mice. Therefore, we hypothesize that CSF acidosis might play a role in the pathophysiology of AQP4-Ab-positive NMO and that alterations in CSF pH might possibly influence the outcome of acute attacks in this condition. In addition, we discuss potential clinical implications and make proposals on how to test the hypothesis. Finally, other factors that influence astrocytic AQP4 membrane expression and might play a role in NMO are discussed.